2020
DOI: 10.3389/fpubh.2020.580757
|View full text |Cite
|
Sign up to set email alerts
|

Health-Related Quality of Life and Its Correlation With Depression Among Chinese Centenarians

Abstract: Background: As evidence on depression and health-related quality of life (HRQoL) among the oldest-old is currently limited, this study aimed to re-examine the association between depression and HRQoL among centenarians. Methods:We analyzed cross-sectional data from the China Hainan Centenarian Cohort Study (CHCCS). The 15-item Geriatric Depression Scale (GDS-15) and three-level EuroQol five-dimensions (EQ-5D-3L) were used to evaluate depression and HRQoL, respectively. Poor health states were defined as EQ-5D … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
18
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 40 publications
4
18
1
Order By: Relevance
“…This study showed that stress has direct and indirect effects on health-related quality of life mediated by shoulder pain, disability, and depression. These results are consistent with those of previous studies [43,47], indicating that the higher the depression, the lower the health-related quality of life, and the higher the pain, the higher the depression and the lower the health-related quality of life [48]. The results of this study suggest that stress directly affects health-related quality of life and causes shoulder pain, shoulder disability, and depression, all of which have direct and indirect effects on health-related quality of life.…”
Section: Discussionsupporting
confidence: 94%
“…This study showed that stress has direct and indirect effects on health-related quality of life mediated by shoulder pain, disability, and depression. These results are consistent with those of previous studies [43,47], indicating that the higher the depression, the lower the health-related quality of life, and the higher the pain, the higher the depression and the lower the health-related quality of life [48]. The results of this study suggest that stress directly affects health-related quality of life and causes shoulder pain, shoulder disability, and depression, all of which have direct and indirect effects on health-related quality of life.…”
Section: Discussionsupporting
confidence: 94%
“…This study showed that stress has direct and indirect effects on HRQoL, mediated by shoulder pain, disability, and depression. These results are consistent with those of previous studies [ 65 , 68 ], indicating that the higher the depression, the lower the HRQoL, and the higher the pain, the higher the depression and lower the HRQoL [ 69 ]. The results of this study suggest that stress directly affects HRQoL and causes shoulder pain, shoulder disability, and depression, all of which have direct and indirect effects on HRQoL.…”
Section: Discussionsupporting
confidence: 93%
“…In this study, it was shown that stress has a direct as well as indirect effect on the health-related quality of life through shoulder pain, shoulder disorder, and depression. The results are consistent with previous studies [47,43], showing that the higher the depression level, the lower the health-related quality of life and the higher the pain, the higher the depression level and the lower the health-related quality of life [48].…”
Section: Discussionsupporting
confidence: 93%